PUSAT PEMBINAAN DAN PENGEMBANGAN E-SPORT DI KOTA BANJARBARU - Munanda, Nafta Widayani; Sarbini, Gusti Novi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Banjarbaru has become a thriving city with various existing communities, from art, food, clothing, conventional sports, and electronic sports, which can invite people from outside the city to come. The electronic sports in Banjarbaru has the potential to be developed as an opportunity to show the local children's potential and have quality players who are no less competitive. Along with the rapid development of E-Sports, and the increasing number of enthusiasts who are highly expected in Banjarbaru, a Guidance and Development are needed to accommodate E-Sport enthusiasts themselves to practice and obtain adequate facilities. The Eco-Futuristic Architecture theme is applied to the design because E-Sport is closely related to technology that has developed until today.